2020
DOI: 10.1002/jcp.29708
|View full text |Cite
|
Sign up to set email alerts
|

Induction and maintenance of specific multipotent progenitor stem cells synergistically mediated by Activin A and BMP4 signaling

Abstract: We recently reported that epiblast stem cells (EpiSCs)‐like cells could be derived from preimplantation embryos (named as AFSCs). Here, we established AFSCs from pre‐implantation embryos of multiple mouse strains and showed that unlike EpiSCs, the derivation efficiency of AFSCs was affected by the genetic background. We then used AFSCs lines to dissect the roles of Activin A (Act A) and basic fibroblast growth factor and reported that Act A alone was capable of maintaining self‐renewal but not developmental po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Furthermore, Socs3, a gene downstream of the LIF pathway, endoderm genes Gata4 and Sox17, and ectoderm-related genes Pax6 and Map2 were significantly increased in the LIF medium than in control ALSCs (Supplementary Figures 2C,D). These data suggested that Act A was important but not sufficient to sustain ALSC growth and self-renewal, which is consistent with previous studies (Ashida et al, 2017;Mulas et al, 2017;Chen et al, 2020). We also show that the combination of Act A and LIF could support the pluripotency of ALSCs.…”
Section: Alscs Display Similar Properties With Episcssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, Socs3, a gene downstream of the LIF pathway, endoderm genes Gata4 and Sox17, and ectoderm-related genes Pax6 and Map2 were significantly increased in the LIF medium than in control ALSCs (Supplementary Figures 2C,D). These data suggested that Act A was important but not sufficient to sustain ALSC growth and self-renewal, which is consistent with previous studies (Ashida et al, 2017;Mulas et al, 2017;Chen et al, 2020). We also show that the combination of Act A and LIF could support the pluripotency of ALSCs.…”
Section: Alscs Display Similar Properties With Episcssupporting
confidence: 92%
“…Previously we reported that Act A is an essential factor for maintaining the self-renewal of EpiSCs (Chen et al, 2020;Wu et al, 2020). To test the role of Act A, CHIR99021 (CHIR), and LIF in primed stem cells, we first cultured AFSCs, which are essentially a cell line similar to EpiSCs (Bao et al, 2018) in a chemically defined medium containing Act A with CHIR (AC medium) or LIF (AL medium).…”
Section: Derivation Of Primed Stem Cells From Post-implantation Embryos Supported By Act a And Lifmentioning
confidence: 99%
“…Considering that the regulation of OCT4 expression of cultured embryos was consistent with the postimplantation EPI, and that the cell fate of ICM cells was changed (with increased proportion of OCT4‐positive cells) (Figure 1E), K2iL and KSOM‐cultured embryos were placed into a chemically defined system respectively to isolate AFSCs lines which are EpiSCs‐like pluripotent stem cells after 48 h (Figure 1A and Figure 2B). Undoubtedly, as in our previous studies [23], AFSCs were acquired at passage 3 and purified at passage 7. It was worth noting that when the number of cell lines was calculated, it was found that 2i/LIF‐treated embryos showed a higher efficiency of deriving AFSCs (29.6%) than untreated embryos (19%) (Table 1), which confirmed our speculation.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of these EpiSCs depends on Activin/Nodal and bFGF signaling pathways. Recently, we have also reported a type of pluripotent s tem c ells deriving from pre‐implantation embryos in feeder‐free chemically defined medium containing A ctivin A and b F GF, termed as AFSCs [19, 23, 24]. The AFSCs show transcriptome characteristic similar to EpiSCs and do not depend on feeder cells or knockout serum replacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation